Resilience of Wives Experienced Inaffair - Elda, Prisicilia; Widyorini, Endang (Journal of Public Representative and Society Provision, 2024)
The main problem that will cause the marriage rate to fall in 2024 is the factor of infidelity, and Indonesia is number two in cases of infidelity in Asia. There are two choices that a wife must make to her husband, namely whether the wife will accept him back or terminate her marriage or divorce. The process of a wife continuing to accept the situation and surviving her husband's affair is a process of resilience. The method used in this research is qualitative research using a phenomenological approach which conducted research on three wives who experienced infidelity, worked alone and still maintained their marriage. The results of the research show that the three subjects have good resilience, because they have reasons to remain resilient, there is a process for the subject to become resilient, forms of resilience and factors that influence them to have good resilience.